The photographer's career guide to shooting production stills for film and television - Downs, Jace, 1978- (Routledge, 2022)
"Based on the author's real-world experience, this book provides a comprehensive guide on how to develop a professional career and client base as a unit stills photographer in the entertainment industry. Industry veteran, Jace Downs, takes readers behind the scenes as he explores production from the perspective of a unit stills photographer. Honest and entertaining, chapters cover the production environment, set etiquette, equipment, dealing with difficult talent, shooting on set, developing a client base, joining the union, and much more. Accessible to those within and outside of the entertainment industry, this book is ideal for intermediate level photographers looking to expand their skillset and client base, as well as for aspiring photographers who would like more insight into photography work in entertainment production"--